The Ecotourism Mangrove Suitability Assessment in Reroroja Village, Magepanda District, Sikka Regency, East Nusa Tenggara, Indonesia - Calumba, Kristianti Rilenitiara; Kangkan, Alexander Leonidas; Toruan, Lumban Nauli Lumban (Journal Omni-Akuatika, 2023)
The mangrove area of Reroroja Village has the potential to be developed into an ecotourism area, because mangroves grow along the coast. This study aims to determine the suitability of mangrove areas as ecotourism areas from April to May 2023. The mangrove area was divided into two observation stations using the purposive sampling method. The study assessed various mangrove tourism suitability parameters, including mangrove thickness, species, density, debris, tides, mangrove fauna, distinctiveness, law/legality, accessibility, visitor presence, facilities, and private-owned institutions. The data was analyzed using the Tourism Suitability Index (TSI) formula, and the average suitability score for Stations I and II was 71.5%. This value falls in the S2 (Suitable) category, indicating the potential for ecotourism development in the area. The study found that the mangrove area has a rich biodiversity, including fish, crabs, molluscs, reptiles, and birds, and is well-suited for ecotourism development.Keywords: Ecotourism, Tourism Suitability Index, Mangrove, Reroroja Village.